Transformational leadership model and academic service quality: An investigation on higher education - Cucun Sunaengsih; Aan Komariah; Dedy Achmad Kurniady; Nugraha Suharto; Dadan Djuanda; Aah Ahmad Syahid; Muthahharah Thahir (Universitas Jambi, Indonesia, 2025)
This research examines the relationship between transformational leadership and academic service quality in higher education. This research adopts a quantitative descriptive research method. There were 506 research samples consisting of the head of the study program, lecturers, staff, and students taken from six regional campuses of Universitas Pendidikan Indonesia, where they were enrolled in the study program for Primary Teacher Education. Primary data were collected using a self-administered questionnaire. Data analysis conducted in this research used the SPSS 24.00 application, which consists of descriptive data analysis, correlation analysis, ANOVA analysis, and regression evaluation. The findings revealed a positive and significant relationship between the nature of the transformational leadership model and the quality of academic services. This research finds further support for the relationship between transformational leadership models and the quality of academic services in higher education.